Behaviour of Precast Column Foundation Connection under Reverse Cyclic Loading - L. Hemamathi; K. P. Jaya (Advances in Civil Engineering)
Precast column foundation connection is one of the critical connections under reverse cyclic loading, and the present study focuses on this connection. Three types of connections were considered, such as (i) base plate connection, (ii) pocket connection, and (iii) grouted sleeve connection. All the above connections were designed, and experimental investigation was carried out on 1 : 2 scaled models by subjecting the column to lateral reverse cyclic loading. Displacement-controlled loading pattern has been adopted for the testing of the specimens. The structural response of the connection was studied for their (i) load-displacement hysteresis behaviour, (ii) stiffness degradation, (iii) energy dissipation, and (iv) ductility. The results were then compared with that of the monolithic connection. The precast connection was more ductile, and the energy dissipated by the pocket connection was high compared to the base plate and grouted sleeve connection. The ductility and the load-carrying of grouted sleeve connection were small compared to other connections. The results of the study showed the precast column foundation can be used in seismic prone areas.